Perancangan Antarmuka Pengguna Sistem Bimbingan dan Konseling berbasis Aplikasi Web menggunakan metode Human Centered Design (Studi Kasus: SMK Muhammadiyah 1 Malang) - Dwi Cahyaningsih; Hanifah Muslimah Az-Zahra; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Guidance and counseling are some of the efforts given by SMK Muhammadiyah 1 Malang in providing assistance services to students. In providing assistance services to students, guidance and counseling teachers need to collect guidance data, but the guidance data collection is still done manually written in books, this creates inefficiency and takes a long time to find the guidance and counseling data needed. The purpose of this study was to design a web application-based guidance and counseling system user interface using the Human-Centered Design (HCD) method. The HCD method is used to design the user interface because this method can understand the needs of system users. The initial stage in the HCD method is the initial data collection which is carried out by interviewing users to understand and determine the user context and determine user needs. Next, design solutions that produce wireframes and prototypes. Then carry out the first and second evaluation activities which are evaluation and improvement, the process is part of the iteration process. The last process in HCD is the final evaluation of the solution design using the System Usability Scale method. The results of the design evaluation get a SUS score of 74.375. From the SUS score, the interface design of the guidance and counseling system is included in the ACCEPTABLE category or feasible and acceptable to users.